2023
DOI: 10.3390/jof9030335
|View full text |Cite
|
Sign up to set email alerts
|

Mucorales and Mucormycosis: Recent Insights and Future Prospects

Abstract: The classification of Mucorales encompasses a collection of basal fungi that have traditionally demonstrated an aversion to modern genetic manipulation techniques. This aversion led to a scarcity of knowledge regarding their biology compared to other fungal groups. However, the emergence of mucormycosis, a fungal disease caused by Mucorales, has attracted the attention of the clinical field, mainly because available therapies are ineffective for decreasing the fatal outcome associated with the disease. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Additionally, this knowledge may lead to novel approaches for rapid diagnosis and treatment, thereby enhancing the ability to treat this challenging fungal infection. [7] Recent research has identified key genes associated with the virulence of Mucorales. These genes, including CotH -like genes, belong to a Mucorales-specific gene family, a high-affinity iron uptake system, azole resistance genes such as cytochrome P450 , and genes involved in the host innate immune response contribute to the complexity of mucormycosis.…”
Section: Mucormycosis and Genetic Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this knowledge may lead to novel approaches for rapid diagnosis and treatment, thereby enhancing the ability to treat this challenging fungal infection. [7] Recent research has identified key genes associated with the virulence of Mucorales. These genes, including CotH -like genes, belong to a Mucorales-specific gene family, a high-affinity iron uptake system, azole resistance genes such as cytochrome P450 , and genes involved in the host innate immune response contribute to the complexity of mucormycosis.…”
Section: Mucormycosis and Genetic Predispositionmentioning
confidence: 99%
“…Understanding the genetic factors that influence disease advancement provides valuable insights into the development of targeted therapies that precisely address the underlying molecular mechanisms of the disease. [7] A comprehensive understanding of genetic factors influencing disease susceptibility and severity can guide the development of public health strategies, including optimized vaccination programs and targeted screening initiatives. This approach aimed to alleviate the overall disease burden on the population.…”
Section: Introductionmentioning
confidence: 99%
“…68,163 R3B2, a potential drug target being unique to Mucorales with its structure and function thoroughly studied, degrades RNA selectively, favoring singlestranded over double-stranded RNA binding domains. 164 R3B2's absence increases drug-resistance in strains via epimutation, indicating NCRIP route compete with the epimutational route. 68 Mutations in rdrp1 and rdrp3 genes also influence epimutant formation.…”
Section: Pathogenesismentioning
confidence: 99%
“…The explosion of MCR cases in the COVID-19 pandemic wave in India during 2021 further stimulated interest in this disease [8]. Tremendous strides have been achieved in deciphering the complex immunopathogenesis of this infection, which are beyond the scope of this review [9,10]. Here, we focus on new information regarding the clinical aspects of MCR during the last 18–24 months…”
Section: Introductionmentioning
confidence: 99%